Life fulfillment: The motivation dynamics of freelancers - Riyono, Bagus; Usman, Rima Fazriah (HUMANITAS published by Universitas Ahmad Dahlan., 2022)
People, in general, would have a career preference to become an employee in a big and established company. This career preference is natural, considering many benefits obtained when a person becomes an employee. However, this does not apply to some individuals who choose freelancers. Even though the stigma of being a freelancer exists, it was not an obstacle for people who choose a freelancer in choosing this career. This study's purpose was to understand the reason and the meaning of the career choices of freelancers. This research employed a qualitative approach with the phenomenological method. The data were collected by interviewing six freelancers that have been full-time freelancers for at least two years in the information technology field. The result showed that freedom, flexibility, learning opportunity, financial security, family time, progressive career, and life fulfillment motivate individuals to become full-time freelancers. The essence of the motivational dynamics of a freelance career was to achieve life fulfillment.